Poverty Alleviation: A Regional Study Of Baubau City - L.M. Azhar Sa'ban; Andy Arya Maulana Wijaya; Harry Fajar Maulana; Eko Satria (Jurnal Mamangan, 2025)
The main problem in this study is that the percentage of poor people in 2023 increased by 0.22 percent compared to 2022. The purpose of this study is to provide an overview of the poverty condition in Kota Baubau. The method used in this research is a mix method, namely qualitative and quantitative. Qualitative analysis was conducted by collecting data using interview techniques to find out the poverty reduction program of Kota Baubau in 2023 which is divided into three clusters, namely the expenditure reduction cluster, the income generation cluster, and the poverty reduction cluster. Quantitative analysis Quantitative analysis was also used to analyze and interpret data obtained from the Central Bureau of Statistics (BPS) of Baubau City and BPS of Southeast Sulawesi. The results showed that Baubau City experienced an increase in the growth of the number of poor people from 12,690 people in 2022, to 13,290 people in 2023. The poverty depth index of Baubau City was documented in 2022 at 0.80, there was an increase in 2023 at 1.21. The poverty severity index of Baubau City was recorded at 0.17 in 2022, but increased again to 0.48 in 2023. The poverty line of Baubau City in 2022 amounted to 376,932 (Rp/Capita/Month) which in 2023 increased by Rp82,031 to Rp412,008. The novelty of this research lies in the use of a mixed methods approach combined with bibliometric analysis and three-cluster strategy mapping in assessing the effectiveness of poverty alleviation programs specifically in Baubau City.